Multifaceted NOS instruction: Contextualizing nature of science with documentary films - Bloom, M.; Binns, I.C.; Koehler, C. (International Journal of Environmental and Science Education, 2015)
This research focuses on inservice science teachers’ conceptions of nature of science (NOS) before and after a two-week intensive summer professional development (PD). The PD combined traditional explicit NOS instruction, numerous interactive interventions that highlighted NOS aspects, along with documentary films that portrayed NOS in context of authentic scientific discovery. Reflective dialogue was used throughout the professional development to encourage constructivist learning. The PD addressed seven commonly held NOS tenets that are deemed significant to K-12 science teachers. Finally, qualitative methodologies were used to analyze the Views of Nature of Science Questionnaire (VNOS-D) and the associated interview data to explore subtleties within each NOS tenet and to gain a richer understanding of how the teachers’ NOS understanding differed before and after the PD. © 2015 by iSER, International Society of Educational Research.
Keywords: Contextualized instruction; Nature of science; Professional development; dept.egm; ⚠️ Invalid DOI

Observations of the Influence of Regional Beach Dynamics on the Impacts of Storm Waves on the Connecticut Coast During Hurricanes Irene and Sandy - Tait, James F.; Ferrand, Ezgi Akpinar (Learning from the Impacts of Superstorm Sandy, 2015)
The Connecticut shoreline is one of the most intensively developed in the country. In many locations, development has relied on the buffering capacity of broad beaches for protection against storms. Much of this development is at risk due to an insufficient understanding of regional beach dynamics. The coast is commonly regarded as “protected” by the presence of Long Island. Nonetheless, Irene and Sandy imposed significant property losses on coastal cities. The most severe damages were due to wave impact in areas with narrow beaches. Small differences (as little as 21 m) in beach width proved to be significant during these storms. Sheltering by Long Island does not prevent coastal erosion during local storms. In the long run, it does prevent the rebuilding of the beach during fair weather by limiting the energy available for shoreward transport. This dynamic makes the beaches naturally erosive and their buffering capacity transient at best.
Keywords: Beach erosion; Beaches; Buffering capacities; Coastal cities; Coastal erosion; Connecticut beach dynamics; Dynamics; Energy asymmetry; Erosion; Fair weather; Hurricane Irene; Hurricane Sandy; Hurricanes; Property loss; Storm wave impacts; Storm waves; Storms; Water waves; beach erosion; dept.egm; energy asymmetry; faculty_collection; storm wave impacts

The emergence of stem - Koehler, C.; Binns, I.C.; Bloom, M.A. (STEM Road Map: A Framework for Integrated STEM Education, 2015)
Journal Abbreviation: STEM Road Map: A Framew. for Integr. STEM Educ.
Keywords: dept.egm

The stem road map for grades k-2 - Koehler, C.; Bloom, M.A.; Milner, A.R. (STEM Road Map: A Framework for Integrated STEM Education, 2015)
Journal Abbreviation: STEM Road Map: A Framew. for Integr. STEM Educ.
Keywords: dept.egm

Residential perspectives: the value of Floodplain‐ buyout open space - Zavar, Elyse (Geographical Review, 2015)
This mixed-methods case study identifies how floodplain property acquisitiona buyoutimpacts an urban environment at the neighborhood scale while considering the role of individual residents in formal and informal land-use decision making. In floodplain buyouts, the reopening of urban space is enabled by federal structural drivers, primarily Federal Emergency Management Agency (FEMA), but it is repurposed as a cultural landscape constructed and produced by individuals. This research explores how residents perceive and ascribe values to the buyout landscape in Lexington, Kentucky. Enabled by federal funds, but left largely to their own devices, residents in Lexington adopted uses, ascribed values, and produced their own land-use norms in each buyout neighborhood.
31 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-849-610-654-018 tex.type: [object Object]
Keywords: dept.egm; floodplain; land management; land value; peer-reviewed; property acquisition

Rainwater Harvesting as an Effective Climate Change Adaptation Strategy in Rural and Urban Settings - Ferrand, Ezgi Akpinar (Managing Water Resources under Climate Uncertainty: Examples from Asia, Europe, Latin America, and Australia, 2015)
Human societies are known for their resilience and ability to adapt to short- and long-term environmental change. Despite their pragmatism and adaptability, humans could be forced to move and/or seek better conditions for survival, especially when climate change and water availability are at issue. This chapter provides case studies on easy-to-adopt rainwater harvesting applications as effective climate change adaptation strategies in rural and urban settings to increase human resiliency.
Citation Key Alias: lens.org/158-085-691-782-246
Keywords: Climate Change Adaptation; Climate change adaptation; Rainwater Harvesting; Rainwater harvesting; Urban and Rural Settings; Urban and rural settings; dept.egm